2017
DOI: 10.1016/j.ypmed.2016.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Associations between demographic characteristics and physical activity practices in Nevada schools

Abstract: Schools are important settings for not only providing and promoting children's physical activity (PA) but also for reducing PA disparities. We investigated associations between school-level demographic characteristics (racial/ethnic and socioeconomic composition, urban-rural status, and student-to-teacher ratio) and 16 PA-promoting practices in 347 Nevada public elementary, middle, and high schools in 2014. We found that low-cost and easy-to-implement practices are most prevalent. There is relative demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…Interestingly, the prevalence of nonmedical prescription pain drugs is higher among adolescents than it has ever been, and data suggest the younger adolescents (middle school) may be particularly affected (Miech, Bohnert, Heard, & Boardman, ). Moreover, data from the NSDUH indicate that adolescents ages 12–17 living in rural areas (6.8%) have 35% greater odds of past‐year prescription opioid misuse than those living in large urban areas (5.3%) (Monnat, Lounsbery, McKenzie, & Chandler, ). A recent systematic review of 15 studies with nationally representative populations found that low family income, poor mental health, and lack of treatment for mental health issues were positively associated with adolescent prescription opioid misuse (Young, Glover, & Havens, ).…”
Section: Substance Use Rates In Adolescentsmentioning
confidence: 99%
“…Interestingly, the prevalence of nonmedical prescription pain drugs is higher among adolescents than it has ever been, and data suggest the younger adolescents (middle school) may be particularly affected (Miech, Bohnert, Heard, & Boardman, ). Moreover, data from the NSDUH indicate that adolescents ages 12–17 living in rural areas (6.8%) have 35% greater odds of past‐year prescription opioid misuse than those living in large urban areas (5.3%) (Monnat, Lounsbery, McKenzie, & Chandler, ). A recent systematic review of 15 studies with nationally representative populations found that low family income, poor mental health, and lack of treatment for mental health issues were positively associated with adolescent prescription opioid misuse (Young, Glover, & Havens, ).…”
Section: Substance Use Rates In Adolescentsmentioning
confidence: 99%
“…Perhaps more concerning is the trends described above disproportionally affect children from disadvantaged backgrounds. Data show that children who go to large, urban schools; schools with a high minority population; and schools with low-income levels are the least likely to get access to recess, and often report the shortest amount of time dedicated to recess (7,8). It is plausible that environmental factors affect children's access to physical activity opportunities in urban and lowincome school systems.…”
Section: Introductionmentioning
confidence: 99%
“…Children who are in a school environment with adequate facilities and infrastructure will be different from children in schools with limited learning facilities. Monnat suggests that School demographic characteristics, including racial/ethnic and socioeconomic (SES) composition, class sizes, and rurality may impact schools' abilities to incorporate PA practices into the school day, resulting in disparities that limit children's opportunities to accrue moderate-to-vigorous physical activity (MVPA) [5].…”
Section: Introductionmentioning
confidence: 99%